Safety and reactogenicity of the combined diphtheria-tetanus-acellular pertussis-inactivated poliovirus-Haemophilus influenzae type b (DTPa-IPV/Hib) vaccine in healthy Vietnamese toddlers: An open-label, phase III study. Issue 3 (3rd March 2016) - Anh, Dang Duc; Van Der Meeren, Olivier; Karkada, Naveen; Assudani, Deepak; Yu, Ta-Wen; Han, Htay Htay
Abstract: The introduction of combination vaccines plays a significant role in increasing vaccine acceptance and widening vaccine coverage. Primary vaccination against diphtheria, tetanus, pertussis, poliomyelitis and Haemophilus influenza type b (Hib) diseases has been implemented in Vietnam. In this study we evaluated the safety and reactogenicity of combined diphtheria-tetanus-pertussis-inactivated polio (DTPa-IPV)/Hib vaccine when administered as a booster dose in 300 healthy Vietnamese children <2 years of age (mean age: 15.8 months). During the 4-day follow-up period, pain (31.7%) and redness (27.3%) were the most frequent solicited local symptoms. Pain (2%) was also the most frequent grade 3 local symptom. One subject reported 2 serious adverse events that were not causally related to the study vaccine. DTPa-IPV/Hib conjugate vaccine was well tolerated as a booster dose in healthy Vietnamese children aged <2 years.